Performance measurement of sustainable third party reverse logistics provider by data envelopment analysis: a case study of an Indian apparel manufacturing group. (2015) - Venkatesh, V.G.; Bhattacharya, Sonali; Sethi, Madhvi; Dua, Sahil
In the current trend, research on reverse logistics domain is gaining its importance and has its own complexity in terms of design and operations, due to several factors. There are several stake holders participating in managing the reverse supply chains. The role of third party service provider in reverse supply chains is imperative and their performance vary according to the various dimensions. Previous studies support and evaluate the relative performance using various multi criteria decision making (MCDM) techniques. The current paper selects one such tool, data envelopment analysis (DEA) using the automated platform STATA to analyse the performance of third party logistics service provider. The study is restricted to the apparel industry domain, a least explored and a dynamic field. The factors to be in this current study are selected through a structured process. The work measures current level of performance in an observed firm which is employing the third party logistics service provider.